THE ROLE OF LEGUMES IN SOIL ENRICHMENT IN AGRICULTURE (Scientific journal of the Fergana State University, 2024)
Grain-legume crops have a great importance in increasing the productivity of land in the national economy. Leguminous plants are considered to be nitrogen-fixing crops in the soil.